2017
DOI: 10.4049/jimmunol.1701174
|View full text |Cite
|
Sign up to set email alerts
|

Infection of Ferrets with Influenza Virus Elicits a Light Chain–Biased Antibody Response against Hemagglutinin

Abstract: The domestic ferret () is a commonly used animal model for the study of influenza virus infection and vaccination. Recently, our group has developed murine mAbs with specificity for the κ (Igκ) and λ (Igλ) L chains of ferret Ig. These mAbs were used to quantify the abundance of Igκ and Igλ in serum and to evaluate L chain usage of the Ab response against the hemagglutinin (HA) protein elicited by influenza infection. After influenza A infection of immunologically naive ferrets with various H1N1 or H3N2 strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 47 publications
0
18
0
Order By: Relevance
“…Full-length HA proteins were developed for each of the Fluozone 2016/17 quadrivalent vaccine components: H1N1, H3N2, Victoria-lineage, and Yamagata-lineage. Chimeric HA proteins were generated with the globular head portion of A/mallard/Sweden/81/2002 (A/H6N2) in the context of A/ California/07/2009 (A/H1N1 pan ) stem (cH6/1) or A/Anhui/1-YK/2013 (A/H7/N2) in the context of A/ Perth/16/2009 (A/H3N2) stem, as previously described (78,79). Correct stem conformation was validated by ELISA using CR6261 or CR8020 stem-directed monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…Full-length HA proteins were developed for each of the Fluozone 2016/17 quadrivalent vaccine components: H1N1, H3N2, Victoria-lineage, and Yamagata-lineage. Chimeric HA proteins were generated with the globular head portion of A/mallard/Sweden/81/2002 (A/H6N2) in the context of A/ California/07/2009 (A/H1N1 pan ) stem (cH6/1) or A/Anhui/1-YK/2013 (A/H7/N2) in the context of A/ Perth/16/2009 (A/H3N2) stem, as previously described (78,79). Correct stem conformation was validated by ELISA using CR6261 or CR8020 stem-directed monoclonal antibodies.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that an abundance of sialylated Fc glycans predicts influenza vaccine efficiency in humans (21). In ferrets, influenza exposure elicits a light chain-biased antibody response against the surface glycoprotein hemagglutinin (HA) (18). The shift of ferret IgG glycan profiles observed in this study might be a programmed inflammatory reaction after exposure to influenza virus or may just reflect an augmented antibody-mediated immune response in infected ferrets or decreased/increased clearance of certain glycoforms.…”
Section: N-glycan Profiles Of Ferret Iggsmentioning
confidence: 63%
“…Because of this human-like respiratory physiology in ferrets, antisera collected from influenzainfected experimental ferrets have been used as reference standards to monitor virus antigenic changes for annual influenza vaccine strain selection (7)(8)(9)(10). However, ferret antibodies have also been shown to target antigenic epitopes on influenza viruses differently than human antibodies (11)(12)(13)(14)(15)(16)(17)(18). This difference between ferret immunity and human immunity is one of the factors responsible for influenza vaccine strain mismatch (7,19).…”
Section: Influenza Viruses Cause Contagious Respiratory Infections Rmentioning
confidence: 99%
“…Before this reagent development, research was limited to characterizing serum and nasal washes for neutralizing antibodies and measuring clinical signs after infection. Therefore, future studies can capture the cellular immune reactions of T-cell responses with IFN-γ ELISAs [120], peripheral blood leukocyte tracking [121], and ELISpots [88,122], as well as the humoral immunity [18,92,123,124].…”
Section: Pre-immunity On the Immune Responsementioning
confidence: 99%